(untitled) (The Review of Diabetic Studies, 2024)
Background Mechanical ventilation is a cornerstone of intensive care for critically ill patients, yet prolonged use increases risks of complications like ventilator-associated pneumonia and ICU length of stay. Nurse-led weaning protocols have emerged as evidence-based strategies to shorten ventilation duration and improve outcomes, shifting from physician-driven to integrated, multiprofessional models.​ Methods This comprehensive review synthesizes evidence from randomized controlled trials, quasi-experimental studies, observational cohorts, qualitative research, and concept analyses on nursing roles in weaning protocols and respiratory therapy. A conceptual framework maps nursing contributions across stabilization, active weaning, and post-extubation recovery.​ Results Nurse-led protocols reduced mechanical ventilation duration by 1-2 days, ICU stays, and ventilator-associated events compared to physician-led care. Key predictors like Rapid Shallow Breathing Index (RSBI <105) and tools such as Burns Wean Assessment Program enhanced weaning success, with nurses pivotal in monitoring, SBTs, and complication prevention across diverse populations.​ Conclusions Empowering nurses through standardized protocols optimizes weaning, reduces burdens, and extends care to long-term recovery. Future efforts should address implementation barriers, AI integration, and global standardization to leverage nursing autonomy fully.​